The Canary Platform for the Reduction of School Absenteeism - Perez-Jorge, David; Ruiz-Ruiz, Jorge; Rodriguez-Jimenez, Maria del Carmen; Arino-Mateo, Eva (International Journal of Education and Practice, 2020)
In 2012, the Canaries School Council (CSC) and the Canary Federation of Municipalities (FECAM) decided to investigate the level of school absenteeism in the Canary Islands. They therefore with the Ministry of Education Canary Islands Government about holding a conference for municipal technical teams on addressing this problem, which is particularly worrying in the Canary Islands. Following a needs analysis, the Canary Platform for the Reduction of Absenteeism was developed, comprising three web pages: i) a social network, for communication and cooperation between municipal technical teams; ii) a repository, for resources, such as protocols, documents, articles, communications, available to download; and iii) Moodle, for offering a 125-hour university course for the technical teams. The Canary Platform for the Reduction of Absenteeism operated between March 2013 and September 2018, beginning with 292 technicians from all the Canarian municipalities and, subsequently extending to other institutions, such as island councils, secondary school teachers, educational and psycho-pedagogical guidance teams, and local police. The level of use of, number of visits to, and number of downloads from the website during the first stage were much higher than the second, when despite not being updated, demand continued, especially for the standardized protocol for school absenteeism. These results proved that municipal teams need technical support, supervision, and guidance.